Sahih Muslim: being traditions of the sayings and doings of the prophet Muhammad AS narrated by his companions and compiled under the title al Jami'us sahih - Imam Muslim (Kitab Bhavan, 1982)
ir, Vol.1,c.1-2;Vol.2,c.1-2;Vol.3,c.1-2;Vol.4,c.1; sn,vol.2,c.3